2018
DOI: 10.1098/rsos.181138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amendments on heavy metal immobilization and uptake by Rhizoma chuanxiong on copper and cadmium contaminated soil

Abstract: An improved method was applied for remediating cadmium and copper co-contaminated soil and reducing the metal concentration in Rhizoma chuanxiong. Pot experiments were conducted with six amendments (composed with bentonite, phosphate, humic acid, biochar, sepiolite powder, etc.). The results showed that soil pH, biological activities (soil enzymatic activities and microbial counts) and R. chuanxiong biomass were greatly improved with the addition of amendments in all treatments, especially in T3 and T6. Also, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 62 publications
0
12
0
1
Order By: Relevance
“…This practice has been found effective, eco-friendly and economical in reducing the toxic metal bio-availability [22,23]. The application of organic amendments such as press mud, compost, and farmyard manures (FYM) improve the soil properties and reduce the toxic metals' bio-availability in contaminated soils [24,25]. The application of organic amendments decreases the metals' availability by forming strong organic complexes with metals [26].…”
Section: Introductionmentioning
confidence: 99%
“…This practice has been found effective, eco-friendly and economical in reducing the toxic metal bio-availability [22,23]. The application of organic amendments such as press mud, compost, and farmyard manures (FYM) improve the soil properties and reduce the toxic metals' bio-availability in contaminated soils [24,25]. The application of organic amendments decreases the metals' availability by forming strong organic complexes with metals [26].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pH has been stated to be the major factor in regulating the uptake of Cd by roots (Rizwan et al, 2012). The rise in soil pH with treatment could be attributed to the functional groups located at the surface of biochar (Xie et al, 2018). According to our findings, Uzoma et al (2011) observed a negative correlation between pH and Cd of the soil in the presence of biochar.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentos realizados por Xie et al (2018) evaluaron 6 enmiendas orgánicas compuestas en la inmovilización del Cd y reportaron una disminución prominente en el contenido de Cd y Cu biodisponible. De manera similar, Hamid et al (2018) evaluaron doce enmiendas (solas y mixtas) para la inmovilización de Cd en el sistema de cultivo de arroz-trigo y encontraron una disminución relativamente mayor en la absorción de la planta por la adición combinada de estiércol.…”
Section: Enmiendas Orgánicas Para Estabilizar El Cadmio En Suelosunclassified